Total cost of carbon capture and storage implemented at a regional scale: northeastern and midwestern United States. Issue 5 (6th October 2020) - Schmelz, William J.; Hochman, Gal; Miller, Kenneth G.
Abstract : We model the costs of carbon capture and storage (CCS) in subsurface geological formations for emissions from 138 northeastern and midwestern electricity-generating power plants. The analysis suggests coal-sourced CO2 emissions can be stored in this region at a cost of 52–60 ton −1, whereas the cost to store emission from natural-gas-fired plants ranges from approximately 80 to 90. Storing emissions offshore increases the lowest total costs of CCS to over 60 per ton of CO2 for coal. Because there apparently is sufficient onshore storage in the northeastern and midwestern United States, offshore storage is not necessary or economical unless there are additional costs or suitability issues associated with the onshore reservoirs. For example, if formation pressures are prohibitive in a large-scale deployment of onshore CCS, or if there is opposition to onshore storage, offshore storage space could probably store emissions at an additional cost of less than 10 ton −1 . Finally, it is likely that more than 8 Gt of total CO2 emissions from this region can be stored for less 60 ton −1, slightly more than the 50 ton −1 Section 45Q tax credits incentivizing CCS.